Tinjauan Hukum Islam Terhadap Kawin Pineng pada Masyarakat Adat Abung Nunyai - Firhan, Firhan; Irawan, Ibnu (Palita: Journal of Social Religion Research, 2020)
Abstract [English]:In the customary of low,  marriage is a matter that is blessed with kinship, family and community. until now some communities have consistently carried out weddings that are based on the culture of the local community. Pineng marriage to Abung Nunyai in North Lampung is one example of this traditional marriage. The author is interested in researching the marriage practices of indigenous Abung Nunyai and a review of Islamic law regarding the practice of traditional marriage. The purpose of this study was to determine the local culture of the community in marriage, as well as the legal status of implementing the practice of marriage. This research is field research, using al-Urf theory and descriptive analysis method.Abstrak[Indonesia]: Secara hukum, adat pernikahan merupakan urusan yang berkaitan dengan kekerabatan, keluarga dan masyarakat, sehingga sampaisaat ini beberapa masyarakat tetap konsisten melaksanakan pernikahan yang berlandasakan kebudayaan masyarakat lokal, salah satunya adalah pernikahan Pineng masyarakat adat Abung Nunyai di Lampung Utara. Hal tersebut yang menarik penulis untuk meneliti terkait  praktik pernikahan masyarakat adat Abung Nunyai dantinjauan hukum Islam mengenai praktik pernikahan adat tersebut. Tujuan penelitian ini adalah untuk mengetahui kebudayaan lokal masyarakat di dalam pernikahan, serta status hukum pelaksanaan praktik pernikahan tersebut. Penelitian ini merupakan penelitian lapangan, dengan menggunakan teori al-Urf dan metode deskriptif analisisustomary of low,  marriage is a matter that is blessed with kinship, family and community. until now some communities have consistently carried out weddings that are based on the culture of the local community. Pineng marriage to Abung Nunyai in North Lampung is one example of this traditional marriage. The author is interested in researching the marriage practices of indigenous Abung Nunyai and a review of Islamic law regarding the practice of traditional marriage. The purpose of this study was to determine the local culture of the community in marriage, as well as the legal status of implementing the practice of marriage. This research is field research, using al-Urf theory and descriptive analysis method.